Structural study by solid-state 71Ga NMR of thin film transistor precursors. Issue 40 (22nd September 2015) - Hammann, Blake A.; Ma, Zayd L.; Wentz, Katherine M.; Kamunde-Devonish, Maisha K.; Johnson, Darren W.; Hayes, Sophia E.
Abstract : 71 Ga NMR yields lineshapes that reflect the different coordination environments in tridecameric "Ga 13− x In x " hydroxo-aquoclusters, [Ga13− x In x (μ3 -OH)6 (μ2 -OH)18 (H2 O)24 ]. Indium substitution is found only in the peripheral "outer" metal sites (shown in green). Abstract : Solid-state 71 Ga NMR was used to investigate the structures of several heterometallic Group 13 hydroxo-aquo clusters, [Ga13− x In x (μ3 -OH)6 (μ2 -OH)18 (H2 O)24 ](NO3 )15 which are envisioned for thin film transistors. The characterization of these clusters in the solid state provides additional information in understanding the synthesis, structure and speciation of these precursors for high-quality, ultrasmooth thin films. Yet important structural information regarding these clusters – including the exact composition, isomeric structure, and coordination environments – were unknown prior to this precise NMR spectroscopy study. These molecular species, termed "Ga 13− x In x ", contain three types of six-coordinate metal sites, with bridging OH − groups and H2 O as capping ligands, and we report results onGa 7 In 6, Ga 8 In 5, Ga 10 In 3, Ga 11 In 2, Ga 12 In 1, andGa 13 . Utilizing two magnetic fields (13.9 T and 21.1 T), the solid-state NMR spectra were interpreted in conjunction with computational modeling (using CASTEP) and simulation of spectral lineshapes (using Dmfit). The metal sites are best represented as distorted octahedra, and they exhibit a range of quadrupolar couplings and asymmetry parameters, which can be addressed using longitudinal strain analysis. Until now, there has been speculation about the sites for transmetallation within the synthetic cluster community. Here, we show that Ga NMR is a powerful technique to monitor the transmetallation of In for Ga in theGa 13− x In x clusters, specifically substituting in the "outer ring" sites, and not the "core" or "middle ring".